‘When Teachers Become Students’: Enhancing the Engagement of Public Senior High School XY Kediri Teachers During Online Learning - Yogie Andreas; Putri Ayu Wiwik Wulandari; Lena Nessyana Pandjaitan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Online learning during the pandemic has reduced teacher engagement at SMAN XY Kediri. The 'When Teachers Become Students' training was to foster teacher engagement. This training used a Sense of Self-efficacy approach (instructional strategies, classroom management, & student engagement). This study used a quantitative approach with the experimental method of pretest-posttest design. The sampling technique used is purposive sampling with a total of 16 participants. Measurements were given before and after the training consisting of the engaged teacher scale by Klassen, Yerdelen, and Durksen (2013). Data were analyzed using paired sample t-test. There was an increase in the score of sense of self-efficacy (sig 0.00 (p<0.05)). It indicates that this training is quite effective in increasing teacher engagement at SMA XY Kediri.